Preventable fractions of cancer incidence attributable to 7-years weight gain in the Norwegian Women and Cancer (NOWAC) study - Marisa da Silva (Nature Portfolio, 2021)
Abstract There is a lack of tangible measures for directed public health action to halt the increase in weight and cancer. We estimated the fraction and preventable cases of all and major body fatness-related cancers attributable to 7-years weight gain (≥ 2 kg). We assessed validated self-reported anthropometrics from 44,114 women aged 34–49 years at the enrolment in 1991–1992 and from a second questionnaire in 1998, with follow-up through December 31, 2015. Over 18 years, 3216 body fatness-related cancers and 2041 deaths were reported. Nearly 70% of women experienced weight gain and the average weight change was 4 kg. We observed a substantial proportional impact of weight gain on pancreatic cancer with a population attributable fraction (PAF) of 41.8% (95% CI 8.1–63.1) and a high absolute impact on postmenopausal breast cancer with 4403 preventable cases (95% CI 1064–7299) and a PAF of 16.8% (95% CI 4.1–27.8), and colorectal cancer with 3857 preventable cases (95% CI 1313–5990) and a PAF of 22.6% (95% CI 7.7–35.1). Avoiding weight gain over seven years in middle adulthood could have prevented a considerable proportion of the cancer burden and thousands of cancer cases in women in Norway.